Assessment of Bacterial Population and Some Physicochemical Properties of Compost in Wukari LGA, Taraba State, Nigeria - Onwu, Clement Alex; Umar, Jamila Yakubu; Aliyu, Patricia James (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
Field studies were conducted at the Teaching and Research Farm, Federal University Wukari, to evaluate the bacterial population and selected physicochemical properties of compost in Wukari, Taraba State, Nigeria. Eight compost treatments were tested: GCP (Gmelina leaf + cow dung + poultry droppings), SGCP (Sawdust + Gmelina leaf + cow dung + poultry droppings), RGCP (Rice husk + Gmelina leaf + cow dung + poultry droppings), MGCP (Maize stalks + Gmelina leaf + cow dung + poultry droppings), GCPU (Gmelina leaf + cow dung + poultry droppings + urea), SGCPU (Sawdust + Gmelina leaf + cow dung + poultry droppings + urea), RGCPU (Rice husk + Gmelina leaf + cow dung + poultry droppings + urea), and MGCPU (Maize stalks + Gmelina leaf + cow dung + poultry droppings + urea). Wood ash, water, and topsoil were added to all treatments. Compost pits (1 m³) were prepared for each treatment, replicated three times in a Randomized Complete Block Design (RCBD). Turning, bacterial enumeration, and temperature recordings were conducted monthly. Results revealed significant variation in bacterial populations, with MGCPU recording the highest counts. Compost temperatures remained below 40°C across all stages, indicating decomposition occurred predominantly within the mesophilic range. Total nitrogen (TN) content varied significantly, with RGCPU yielding the highest TN value. Available phosphorus was moderate across treatments, while potassium levels showed no significant difference. Overall, RGCPU and MGCPU outperformed other treatments in terms of microbial activity and nutrient content. Thus, RGCPU is recommended as the most suitable composting treatment for the study area.